Selected issues in Islamic economics education and the way forward - Haneef, Mohamed Aslam; Barom, Mohd Nizam (Centre for Islamic Economics, International Islamic University Malaysia & International Institute of Islamic Thought, 2013)
The past recent decades witnessed a steady growth of ‘Islamization of knowledge’ efforts in the wake of intellectual resurgence of the Muslim world, not least in the discipline of economics. Since the 1980s, there have been an increasing number of institutions around the world attempting to offer courses and programs in Islamic economics (and since the 1990s in Islamic Banking and Finance). Despite the encouraging progress so far, literature specifically in the area of Islamic economics education is rather limited. This chapter seeks to highlight selected critical issues that have arisen in the teaching of Islamic economics as reflected by the experiences of the Southeast Asian universities, namely the Quality of human resources involved in the delivery of the integration and Islamization efforts and the availability of reference materials to support the teaching and learning process. In view of these issues, the chapter also attempts to offer some possible avenues to find solutions to these challenges, as well as planning for the future of Islamic economics education. In this context, the chapter discusses the importance of developing an Usul (methodology) for Islamic economics, which takes into account various aspects of Islamic heritage concerning economic dealings, behavior and institutions beyond the realm of the fiqhi (legalistic) aspect of the Shari’ah. Finally, the chapter highlights the need for regional cooperation to further strengthen the collective efforts in the development of Islamic economics education, particularly in the Southeast Asian region.